Building proofreading skills - Graham, Leland; McCoy, Isabelle (Nashville, TN : Incentive Publications, 1999)
Contains a guide to teaching proofreading skills, information on spelling and grammar, and a variety of illustrated exercises that help students practice recognizing and correcting writing errors.
Professional
Keywords: English language -- Composition and exercises -- Study and teaching; Proofreading -- Study and teaching; Teaching -- Aids and devices; English language -- Composition and exercises -- Study and teaching; Proofreading -- Study and teaching; Teaching -- Aids and devices